First population norms for the EQ-5D-3L in the Russian Federation - Khabibullina, A; Aleksandrova, E; Gerry, CJ; Vlassov, V (Public Library of Science, 2022)
Purpose The EQ–5D survey instrument is routinely applied to general and patient specific populations in many countries, as a means of measuring Health Related Quality of Life (HRQOL) and/or informing Health Technology Assessment. The instrument is the subject of growing interest in the Russian Federation, as too is Health Technology Assessment. This research is the first to systematically present the EQ–5D–3L nationally representative population norms and to examine the socioeconomic and socio-demographic characteristics of the instrument among a representative sample of the Russian population.